Fast route to obtain Al2O3-based nanocomposites employing graphene oxide: Synthesis and sintering. (April 2015) - Benavente, R.; Pruna, A.; Borrell, A.; Salvador, M.D.; Pullini, D.; Peñaranda-Foix, F.; Busquets, D.
Graphical abstract: FE-SEM images of fracture surfaces of the sintered composites: (a) conventional and (b) microwave technique. Highlights: Ultrasonication and freeze drying were used to disperse GO into Al2 O3 matrix. Al2 O3 –rGO powders were densified by conventional and microwave sintering. Microwave technology resulted in smaller grain size than conventional one. Presence of rGO in the composites resulted in improved electrical properties. Abstract: A fast approach based on microwave technology was employed for the sintering of novel composites of alumina and using graphene oxide (GO) as susceptor. The thermal stability and structure of GO materials produced by chemical oxidation of graphite were characterized. The morphology, structure and mechanical properties of the composites sintered by microwave approach were reported to the counterparts sintered by conventional method. The results indicated the formation of an inter-connecting graphene network promoted the electrical conductivity in the composite having only 2 wt.% GO. Hardness and elastic modulus decreased significantly in samples sintered by conventional method due to lower values of density while microwave technology allowed to achieve a positive effect on the densification and showed a smaller grain size when compared to the one achieved by conventional heating.